Evaluation of Oxide Layer Thickness (ZnO, Al₂O₃, BaTiO₃, TiO₂) as an Interlayer and Sensitive layer in SPR Sensors - Freygieon Ogiek Rizal Sukma; I Made Satriya Wibawa; Hangga Novian Adi Putra; Putu Gede Agus Krisna Yogantara (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Numerical simulation of a Surface Plasmon Resonance (SPR) sensor was carried out using COMSOL Multiphysics 5.5 based on the Finite Element Method (FEM) to evaluate detection performance influenced by oxide type and thickness acting as interlayer and sensitive layer. The sensor configuration employs silver (Ag) as the plasmonic metal, while ZnO, Al₂O₃, BaTiO₃, and TiO₂ are considered as oxide materials. The presence of an oxide layer with a certain thickness gives different resonance curve characteristics due to changes in the resulting plasmonic coupling. In this study, BaTiO₃ with a thickness of 40 nm obtained the optimum condition with a minimum FWHM value, accompanied by high FOM value of around 107.75 RIU⁻¹. Meanwhile, the use of oxide materials as sensitive layers causes a shift of the resonance angle toward higher values with increasing refractive index and thickness, resulting in enhanced angular sensitivity. However, this improvement is accompanied by a broadening of the FWHM, indicating increased plasmon damping associated with the sensitive layer. Among the evaluated configurations, the BaTiO₃ (40 nm)/Ag (50 nm)/Al₂O₃ (10 nm) structure exhibits the lowest minimum reflectance and a FOM of 91.35 RIU⁻¹. Despite a marginal reduction in the FOM, the sensitivity attains about 150°/RIU, exceeding that of the configuration without a sensitive layer (120°/RIU). Field profile reveals reduced penetration depth, indicating surface-confined electromagnetic fields beneficial for gas sensing. This study provides insight into the dual role of oxide layers as interlayers and sensitive layers for optimizing electromagnetic confinement, sensitivity, and design strategy for SPR-based gas sensing platforms.